Assessing the Relationship Between Auditor Independence and Audit Quality: A Case Analysis of Six Firms in Bandung - Shelly Dhene Junia; Siti Mialasmaya; Adam Ramdani (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This research examines the significant impact of Auditor Independence on Audit Quality, with a focus on public accounting firms in Bandung. The primary objective of the study is to determine whether a notable relationship exists between these two variables. To measure Auditor Independence (variable X), the study employs indicators such as independence in audit programs, investigations, and reporting. For Audit Quality (variable Y), it utilizes indicators including general standards, fieldwork standards, and reporting standards. The research employs a descriptive method, gathering data through questionnaires that are analyzed using the Statistical Package for the Social Sciences (SPSS). This analysis aims to identify the relationship between Auditor Independence and Audit Quality. The regression analysis yields an equation indicating that an increase in variable X has a positive influence on Audit Quality. The correlation coefficient between Auditor Independence and Audit Quality demonstrates a strong relationship, leading to a significant contribution of Auditor Independence to Audit Quality. The remaining influence is attributed to other unexamined variables. The novelty of this research lies in its specific focus on public accounting firms in Bandung, providing valuable insights into the importance of auditor independence in enhancing audit quality. The implications of this study underscore the importance for firms to prioritize auditor independence in order to enhance overall audit performance.